The New Russian Budget System : A Critical Assessment and Future Reform Agenda - Diamond, Jack (IMF Working Papers; Working Paper ;, 2002)
This paper documents the main elements of the new budget system established in the Russian Federation through its revised budget system law, or the Budget Code, of 2000. It critically examines the budget preparation, budget approval, and budget execution processes, as well as the financial management and planning procedures that underlie the Budget Code. Based on this analysis, recent developments are discussed and a future reform agenda is indicated.